In situ decoration of ZnxCd1−xS with FeP for efficient photocatalytic generation of hydrogen under irradiation with visible light - Zhu, Xianglin (2019)
FeP as a noble‐metal‐free catalyst has been successfully decorated onto the ZnxCd1−xS photocatalyst surface through an in situ phosphating process. In particular, the 2 % FeP/Zn0.5Cd0.5S−P sample showed the best hydrogen generation activity of 24.45 mmol h−1 g−1 which is over 130 times higher than that of pure Zn0.5Cd0.5S and nearly 1.3 times higher than that of the 1 % Pt‐loaded Zn0.5Cd0.5S−P sample. The apparent quantum yield (AQY) of the 2 % FeP/Zn0.5Cd0.5S−P was estimated to be over 10 % at wavelengths up to 470 nm. The fluorescence spectra and electrochemical measurement results suggest that the decorated FeP not only reduces the overpotential for H2 evolution but also promotes the separation of the photogenerated charge carriers through formation of a heterojunction with Zn0.5Cd0.5S, which eventually leads to the superior activity of the FeP/Zn0.5Cd0.5S−P photocatalyst for visible‐light‐driven hydrogen generation.